2017
DOI: 10.1097/igc.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Clear Cell Carcinoma

Abstract: The high rate of upstaging after surgery highlights the importance of lymph node assessment. The high rate of distant recurrence questions the effectiveness of current CT regimens and warrants the development of novel systemic approaches. The role of adjuvant RT deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Creasman et al [8] reported that 15% of patients with UCCC had no MMI with a 5-year OS rate of 83%. The prevalence of non-invasive UCCC has been reported to be 14%–16% in previous studies [610]. However, Abeler and Kjørstad [5] reported that 90% of women with no MMI survived 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Creasman et al [8] reported that 15% of patients with UCCC had no MMI with a 5-year OS rate of 83%. The prevalence of non-invasive UCCC has been reported to be 14%–16% in previous studies [610]. However, Abeler and Kjørstad [5] reported that 90% of women with no MMI survived 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al [10] reported that adjuvant treatment may not be needed in stage I UCCC confirmed with surgical staging, particularly for those with lower risk factors such as superficial MMI and no LVSI. Maggino et al [18] suggested that both chemotherapy and radiotherapy might be unnecessary in patients with stage IA and IB, in their cohort of 65 women with UCCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a multi-institute review of patients with UCCC and no gross evidence of extrauterine disease, it was shown that 52% (39/69) had their disease upstaged at the time of surgery [4]. Similarly, Nguyen et al [5] revealed that 46% (59/129) of patients with clinical stage I UCCC had extrauterine spread. These reports support the argument that UCCC can spread early, including to the lymph nodes and omentum.…”
mentioning
confidence: 99%